Kampanye Gizi Seimbang Melalui Kesenian Rabab - John Amos (Jurnal Sehat Mandiri, 2018)
ABSTRACT The prevalence of underweight children under five in Indonesia is still high, compared to the target of Indonesia's MDGs of 18.5% West Sumatra is still below the target. Health problems can not only be solved by the government, but community involvement is required, therefore the potential needs to be mobilized. Rabab is a traditional Minangkabau traditional string instrument made from coconut shell. With this rabab can be channeled one's musical talents. Usually in this rabab narrated a variety of nagari stories or known by the term Kaba.merupakan a traditional theater that is populist in Minangkabau area, West Sumatra. Research with qualitative approach with research strategy "Case Study Research (CSR)" with descriptive case study. The study was planned to be conducted on 10 (ten) rabab players active in the Balai Selasa, Pesisir Selatan District. Most informants stated that the balanced nutrition message can be compiled into story through Rabab, almost all informants stated that balanced nutrition messages can be prepared according to the language of the community local, most informants stated that the message of balanced nutrition can be compiled according to the dialeg minang community, most informants stated that the message of balanced nutrition can be compiled by summarizing information in simple form, Rabab as a regional art that has the potential Minangkabau have the potential to campaign balanced nutrition in achieve optimal health for children under five and family. It is recommended to review the balanced nutrition messages for the various ages of the community through Rabab art, to examine the influence of Rabab arts interventions on the knowledge, attitude and actions of people of all ages on balanced nutrition, to formulate strategies for the development of Rabab art through the preparation of scenarios for changes in community behavior about balanced nutrition. Keywords: nutrition, rabab